ACTR-29. KETOGENIC DIETS AS AN ADJUVANT THERAPY IN GLIOBLASTOMA (KEATING): A MIXED METHOD APPROACH TO ASSESSING TRIAL FEASIBILITY. (5th November 2018) - Martin-McGill, Kirsty; Cherry, Gemma; Marson, Anthony; Smith, Catrin Tudur; Jenkinson, Michael
Abstract: BACKGROUND: There is increasing interest in the use of ketogenic diets (KD) as adjuvant therapy for glioblastoma (GBM). This trial aimed to: (i) investigate protocol feasibility, (ii) measure patient/carer acceptability and (iii) inform phase III trial design. METHODS: A prospective, randomised, feasibility study, with an embedded qualitative design. Twelve newly diagnosed GBM patients were randomised to the modified ketogenic diet (MKD) or the medium chain triglyceride ketogenic diet (MCTKD). Primary outcome was retention; secondary outcomes included recruitment rate, side effects, extent of ketosis and dietary acceptability, assessed at 12 weeks and 12 months. Semi-structured interviews were conducted with a representative sample of patients and relatives (n=15). RESULTS: Recruitment was achieved within the defined timeframe of 12 months; 42 patients were eligible, of which 12 were recruited (29% recruitment rate). Retention was poor; of the 12 patients randomised, 4 completed the 12-week dietary trial (3 on MCTKD; 1 on MKD). Median duration on diet was 36.5 days (range 0–49) for those who discontinued prior to 12 weeks (n=8). Those who completed the 12-week intervention (n=4) achieved ketosis (1.65mmol/L 1.3mmol/L). No dietary related serious adverse events occurred. Qualitative interviews revealed patients who completed the 12-week diet consented without hesitation. Those who declined participation pre-empted the issues experienced by those who withdrew prior to 12-weeks; namely high levels relative/carer burden and social exclusion. Retainers had a positive experience and reported the diet became the new normal. Patients stated that the 3-month diet duration was too long, but 6 weeks would be more attainable. CONCLUSION: Recruitment to a GBM ketogenic trial is feasible. Retention at 3 months was poor due to the diet negatively impacting patient lifestyle and causing burden for relatives. To assess efficacy in a phase III trial, a 6-week dietary intervention would be advantageous.